Demographic and clinical characteristics of people diagnosed with active sexually transmitted infections among monkeypox cases in Brazil: the 2022 outbreak - Souza, Isabella Nepomuceno de; Pascom, Ana Roberta Pati; Spinelli, Matheus Funke; Dias, Guilherme Borges; Barreira, Draurio; Miranda, Angélica Espinosa (Revista do Instituto de Medicina Tropical de São Paulo, 2024)
The worldwide monkeypox (mpox) outbreak in 2022 showed a high frequency of sexually transmitted infections (STI). A cross-sectional study was carried out using secondary data from the Brazilian official mpox surveillance systems. A total of 10,169 mpox cases were identified, with a median age of 32 years. Among them, 92.3% were male at birth and 57.5% were men who have sex with other men (MSM). Approximately 11% were diagnosed with STI, including 5.8% with syphilis and 2.5% with genital herpes. Individuals aged from 25 to 34 years, MSM, individuals with HIV-positive status, and those manifesting skin eruptions or penile edema were associated with STI. Laboratory investigation for mpox must be implemented as a priority in STI clinics (especially for MSM) to mitigate neglected cases, ensure appropriate treatments, and prevent misdiagnoses.